Oxytetracycline resistant bacteria in Clarias gariepinus and Clarias batrachus larvae and the environment - Goondi Bharathkumar; Thangapalam Jawahar Abraham (Journal of Fisheries, 2015)
Antibiotics and several other chemicals are used in catfish aquaculture as a remedy for various diseases. Reports on the distribution of different groups of bacteria especially the antibiotic resistant bacteria in catfish nursery system are scanty. The present study quantified motile aeromonads, pseudomonads and antibiotic (oxytetracycline) resistant bacteria in Clarias gariepinus and C. batrachus larvae and the rearing water from five catfish nurseries of West Bengal, India between March 2007 and July 2007. The C. gariepinus and C. batrachus larvae recorded mean counts of log 7.26±0.18/g and log 6.24±0.64/g, log 6.37±0.41/g and log 4.93±0.51/g, log 5.46±0.22/g and log 4.38±0.53/g and, log 6.27±0.64/g and log 5.57±0.12/g, respectively for total viable bacteria (TVCs), motile aeromonads (MACs), presumptive pseudomonads (PPCs) and oxytetracycline resistant bacteria (ARBCs). The levels of TVCs, MACs, PPCs and ARBCs were significantly high in C. gariepinus than in C. batrachus larvae. The rearing water recorded comparatively low bacterial counts than in larvae. The difference between the TVCs of larvae and larval rearing water of C. gariepinus was statistically significant, where as it was insignificant for C. batrachus. The mean proportion of motile aeromonads of C. gariepinus larvae and rearing water was about 4-5 fold higher than in C. batrachus.